United States Capitol (Washington, D.C.) records - United States Capitol (Washington, D.C.)
Manuscript volume recording names of tradesmen and the hours and location of their work during the rebuilding of the U.S. Capitol in Washington, D.C., following its burning by the British during the War of 1812.
Collection material in English.
Keywords: Building trades -- Washington (D.C.); United States -- Capital and capitol; Washington (D.C.) -- History -- Capture by the British, 1814.